Antifungal and Antibiofilm Activities of B-Type Oligomeric Procyanidins From Commiphora leptophloeos Used Alone or in Combination With Fluconazole Against Candida spp. - Dantas-Medeiros, Renato; Zanatta, Ana Caroline; de Souza, Luanda Bárbara Ferreira Canário; Fernandes, Júlia Morais; Amorim-Carmo, Bruno; Torres-Rêgo, Manoela; Fernandes-Pedrosa, Matheus de Freitas; Vilegas, Wagner; Araújo, Thiago Antǒnio de Sousa; Michel, Sylvie; Grougnet, Raphaël; Chaves, Guilherme Maranhão; et al. (Frontiers in Microbiology, 2021)
Commiphora leptophloeos (Burseraceae) is a medicinal plant native to Brazil which is popularly used for treating oral and vaginal infections. It has been no scientific evidence pointing to its efficacy in the treatment of these infections. Thus, this study sought to investigate the cytotoxic, antifungal, and antibiofilm activity of C. leptophloeos against Candida spp and to isolate, identify and quantify the content of B-type oligomeric procyanidins (BDP) in the extract of C. leptophloeos stem bark. The extract and the n-butanol fraction were obtained by maceration and liquid-liquid partition, respectively. Phytochemical analysis performed by HPLC-PDA/ELSD and FI-ESI-IT-MS/MS allowed the identification and quantification of BDP in the samples. The application of centrifugal partition chromatography helped isolate BDP, which was identified by 1H NMR and MS analyses. Candida spp. reference strains and clinical isolates (including fluconazole-resistant strains) derived from the blood cultures of candidemic patients and the vaginal secretion of patients with vulvovaginal candidiasis were used for evaluating the antifungal and antibiofilm effect. Minimal inhibitory concentration (MIC) and minimal fungicidal concentration (MFC) were determined by the microdilution technique, and biofilm inhibition was evaluated through the crystal violet and XTT assays. The combined action of BDP with Fluconazole was determined by the checkerboard method. The extract, the n-butanol fraction and the BDP exhibited antifungal activity with MIC values ranging from 312.5 to 2500 μg/mL and were found to significantly reduce the biofilm formed in all the Candida strains investigated. BDP showed a fungicidal potential against strains of Candida spp. (especially against fluconazole-resistant strains), with MIC and MFC values ranging from 156.2 to 2500 μg/mL. In addition, the combined application of BDP and fluconazole produced synergistic antifungal effects against resistant Candida spp. (FICI=0.31-1.5). The cytotoxic properties of the extract samples evaluated in human erythrocytes through hemolytic test did not show hemolytic activity under active concentrations. The findings of the study show that C.leptophloeos has antifungal and antibiofilm potential but does not cause toxicity in human erythrocytes. Finally, BDP, which was isolated for the first time in C.leptophloeos, was found to exhibit antifungal effect against Candida spp. either when applied alone or in combination with fluconazole.